Expanding the Phenotypic Spectrum of ECEL1-Associated Distal Arthrogryposis - Akshata Huddar; Kiran Polavarapu; Veeramani Preethish-Kumar; Mainak Bardhan; Gopikrishnan Unnikrishnan; Saraswati Nashi; Seena Vengalil; Priyanka Priyadarshini; Karthik Kulanthaivelu; Gautham Arunachal; Hanns Lochmüller; Atchayaram Nalini (MDPI AG, 2021)
Distal arthrogryposis type 5D (DA5D), a rare autosomal recessive disorder, is caused by mutations in ECEL1. We describe two consanguineous families (three patients) with novel ECEL1 gene mutations detected by next-generation sequencing (NGS). A 12-year-old boy (patient 1) presented with birth asphyxia, motor developmental delay, multiple joint contractures, pes planus, kyphoscoliosis, undescended testis, hypophonic speech with a nasal twang, asymmetric ptosis, facial weakness, absent abductor pollicis brevis, bifacial, and distal lower limb weakness. Muscle MRI revealed asymmetric fatty infiltration of tensor fascia lata, hamstring, lateral compartment of the leg, and gastrocnemius. In addition, 17-year-old monozygotic twins (patients 2 and 3) presented with motor development delay, white hairlock, hypertelorism, tented upper lip, bulbous nose, tongue furrowing, small low set ears, multiple contractures, pes cavus, prominent hyperextensibility at the knee, hypotonia of lower limbs, wasting and weakness of all limbs (distal > proximal), areflexia, and high steppage gait. One had perinatal insult, seizures, mild intellectual disability, unconjugated eye movements, and primary optic atrophy. In the twins, MRI revealed extensive fatty infiltration of the gluteus maximus, quadriceps, hamstrings, and anterior and posterior compartment of the leg. Electrophysiology showed prominent motor axonopathy. NGS revealed rare homozygous missense variants c.602T > C (p.Met201Thr) in patient 1 and c.83C > T (p.Ala28Val) in patients 2 and 3, both localized in exon 2 of ECEL1 gene. Our three cases expand the clinical, imaging, and molecular spectrum of the ECEL1-mutation-related DA5D.